Bayesian Inference and Maximum Entropy Methods in Science and Engineering : MaxEnt 37, Jarinu, Brazil, July 09-14, 2017 /: MaxEnt 37, Jarinu, Brazil, July 09-14, 2017. ([2018]) - Unknown
No abstract available